2022
DOI: 10.1177/14705958221081636
|View full text |Cite
|
Sign up to set email alerts
|

Paternalistic leadership, employee creativity, and retention: The role of psychological empowerment

Abstract: Drawing upon the cognitive evaluation theory, this study examined the relationship among the three dimensions of paternalistic leadership, namely, authoritarianism, benevolence, and morality on both employee creativity and intention to stay. Data from 344 subordinates and 132 leaders/supervisors were collected from 32 SMEs in the manufacturing industry of Ghana. The findings of the study revealed that while authoritarian leadership has a negative relationship with creativity, benevolent leadership impacts posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Also, subordinates with low psychological empowerment may not feel empowered to follow business ethics strictly (Muniandi et al, 2021). In this regard, Gyamerah et al (2022) found that benevolent leadership combined with psychological empowerment can enhance employees' creativity and their intention to stay. Mubarak et al (2022) also examined the role of ethical leadership in project management and found that ethical leadership promotes project success directly and along with psychological empowerment as well.…”
Section: Moderating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Also, subordinates with low psychological empowerment may not feel empowered to follow business ethics strictly (Muniandi et al, 2021). In this regard, Gyamerah et al (2022) found that benevolent leadership combined with psychological empowerment can enhance employees' creativity and their intention to stay. Mubarak et al (2022) also examined the role of ethical leadership in project management and found that ethical leadership promotes project success directly and along with psychological empowerment as well.…”
Section: Moderating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Another study indicated that transformational leadership greatly contributes to the linkage between organizational innovation at the corporate level and creativity at the individual level (Al Harbi et al, 2019). Psychological empowerment mediates the relationship between benevolent leadership and employee creativity in the dyadic relationship of 344 subordinates and 132 leaders/supervisors from 32 SMEs in the manufacturing industry of Ghana (Gyamerah, He, Asante, Ampaw, & Gyamerah, 2022). Transformational leadership can intrinsically motivate employees and play a crucial role in promoting individual employee creativity (Żywiołek et al, 2022).…”
Section: The Mediating Effect Of Person-supervisor Fit On the Relatio...mentioning
confidence: 99%
“…Paternalistic leadership, which has its roots in Chinese Confucianism (Hou et al, 2019), is a very distinct leadership style that formed in Western society . According to Gyamerah et al (2022), paternalistic leadership is defined as a leadership style combining strict authority, fatherly kindness, and moral integrity with three dimensions: authoritarianism, benevolence, and moral leadership. Authoritarian leadership usually implies specific rewards, punishments, centralized power, and absolute control of leadership behaviors influenced by the ancient Chinese hierarchy (Chen et al, 2018).…”
Section: The Relationship Between Perceived Paternalistic Leadership ...mentioning
confidence: 99%
“…Benevolent leadership refers to behaviors in which leaders show holistic concern for individual employees and their families, manifested in individual care and compassionate tolerance (Farh & Cheng, 2000;Gyamerah et al, 2022). Leaders show genuine kindness and care for their subordinates, which creates gratitude and further enhances subordinates' compliance (Lee et al, 2023).…”
Section: The Relationship Between Perceived Paternalistic Leadership ...mentioning
confidence: 99%